Piezoelectric material-carbon nanotube composite catalyst, lithium-sulfur battery and preparation method of lithium-sulfur battery

By using piezoelectric material-carbon nanotube composite catalyst and ultrasonic treatment in lithium-sulfur batteries, the problems of poor circulation performance and low capacity of lithium-sulfur batteries are solved, and the dynamics and cycling performance of the battery are significantly improved.

CN119819284APending Publication Date: 2025-04-15SOUTHWEST UNIV OF SCI & TECH SICHUAN TIANFU NEW AREA INNOVATION RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070714.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing lithium-sulfur batteries have poor cycling performance and low capacity due to shuttle effect, volume expansion and electrochemical reaction kinetics.

Method used

The catalyst is prepared by ball mill dispersion technology using piezoelectric material-carbon nanotube composite catalyst, and the catalyst is used in the positive electrode material of lithium sulfur batteries, combined with ultrasonic treatment to enhance the piezoelectric effect.

Benefits of technology

It effectively alleviates the impact of slow electrochemical reaction kinetics, shuttle effect and volume expansion on battery circulation performance, and improves the capacity and circulation performance of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819284A_ABST
    Figure CN119819284A_ABST
Patent Text Reader

Abstract

The invention discloses a piezoelectric material-carbon nanotube composite catalyst, a lithium-sulfur battery and a preparation method of the lithium-sulfur battery, and belongs to the technical field of lithium-sulfur batteries. The piezoelectric material-carbon nanotube composite catalyst prepared from carboxylated multi-walled carbon nanotube powder and cubic phase barium titanate powder has the surface properties of high strength, high conductivity, high thermal conductivity, chemical stability and low density, and also shows the piezoelectric catalysis characteristic. The lithium-sulfur battery prepared by utilizing the piezoelectric material-carbon nanotube composite catalyst not only embodies the catalytic property of the intrinsic transition metal oxide, but also has a piezoelectric catalytic effect triggered by internal stress generated in the process that sulfur is evolved into lithium sulfide, and the effect can be further enhanced under the application of an ultrasonic cavitation external field; the problems of poor cycle performance and low capacity caused by shuttle effect, volume expansion and electrochemical reaction kinetics can be effectively relieved, and the preparation method has a good application prospect in lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to a piezoelectric material-carbon nanotube composite catalyst, a lithium-sulfur battery and a preparation method thereof. Background Art

[0002] In recent years, Li-S batteries with lithium metal as negative electrode and sulfur as positive electrode materials are considered to be one of the most promising next-generation high-performance electrochemical energy storage devices due to their extremely high theoretical discharge capacity and energy density, as well as low cost and environmental friendliness. However, there are problems to varying degrees in the components of Li-S batteries. For the negative electrode, uncontrollable lithium dendrite growth caused by uneven lithium ion deposition / stripping may lead to internal short circuits and further fire hazards; for the electrolyte, ether electrolyte is not suitable for large-scale commercial production due to its volatility and flammability. For the sulfur positive electrode, the intrinsic properties of elemental sulfur such as electronic insulation and low ion conductivity reduce the utilization efficiency of sulfur, and the electrode structure and conductive environment are severely decayed, destroying the interface structure and working state of metallic lithium. Suitable external field-assisted lithium-sulfur batteries can not only assist in anchoring polysulfides, but also effectively accelerate the nucleation and decomposition of Li2S and promote the redox reaction of polysulfides. In order to make lithium-sulfur batteries have more reliable commercial application prospects, it is urgent to develop a preparation method that can optimize the special application environment and external field-assisted engineering of lithium-sulfur batteries. Summary of the invention

[0003] In order to solve the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a piezoelectric material-carbon nanotube composite catalyst, a lithium-sulfur battery and a preparation method thereof, so as to solve the problems of poor cycle performance and low capacity of existing lithium-sulfur batteries caused by shuttle effect, volume expansion and electrochemical reaction kinetics.

[0004] The technical solution of the present invention to solve the above technical problems is as follows: a piezoelectric material-carbon nanotube composite catalyst is provided, comprising carboxylated multi-walled carbon nanotube powder and tetragonal barium titanate powder; wherein the purity of the carboxylated multi-walled carbon nanotube is 80%-99%, the diameter is 4nm-10nm, the length is 5μm-30μm, and the oxygen content is >5wt%; the particle size of the tetragonal barium titanate powder is 20nm-500nm, and the microscopic morphology is stick-shaped or spherical; the mass ratio of the carboxylated multi-walled carbon nanotube powder to the tetragonal barium titanate powder is 7:1-14.

[0005] The present invention provides a method for preparing the above-mentioned piezoelectric material-carbon nanotube composite catalyst, comprising the following steps: mixing carboxylation multi-walled carbon nanotube powder and tetragonal barium titanate powder, and preparing the mixture by ball milling.

[0006] Furthermore, the ball milling is carried out at 10°C-50°C and 1000rpm-30000rpm; the single working time of the ball milling is 10min-20min, and the intermittent time is 10min-30min; the total ball milling time is 3h-12h.

[0007] The present invention provides a lithium-sulfur battery, comprising the above-mentioned piezoelectric material-carbon nanotube composite catalyst.

[0008] Furthermore, the lithium-sulfur battery is a button cell or a soft pack cell.

[0009] The present invention also provides a method for preparing the above-mentioned lithium-sulfur battery, comprising the following steps: (1) Mixing active sulfur and the above-mentioned piezoelectric material-carbon nanotube composite catalyst, and then heating to perform low-temperature sulfur melting to obtain a S / C / BTO-T mixture; (2) adding a binder and a solvent to the S / C / BTO-T mixture obtained in step (1), mixing them evenly, and preparing a positive electrode slurry; (3) coating the positive electrode slurry obtained in step (2) on the surface of the positive electrode material, and then cutting the positive electrode material into pieces to obtain a positive electrode sheet; (4) Assemble the lithium-sulfur battery in the order of positive electrode sheet, separator, lithium sheet, gasket and shrapnel, and then perform ultrasonic treatment.

[0010] Furthermore, in step (1), the time for low-temperature sulfur melting is 20-24 hours, the temperature is 155°C-195°C, and the heating rate is 3°C / min-10°C / min.

[0011] Furthermore, in step (1), the active sulfur is single-substance nano-sulfur powder with a size of 80-100 nm; and the mass ratio of the active sulfur to the piezoelectric material-carbon nanotube composite catalyst is 3-5:1.

[0012] Furthermore, in step (2), the binder is polyvinylidene fluoride or LA133 type water-based adhesive; and the solvent is N-methylpyrrolidone or water.

[0013] Furthermore, in step (2), the mass ratio of the S / C / BTO-T mixture, the binder and the solvent is 9:1:18-45.

[0014] Furthermore, the power of the ultrasonic treatment in step (4) is 180-720W.

[0015] The present invention has the following beneficial effects: (1) The piezoelectric material-carbon nanotube composite catalyst prepared by the present invention uses a piezoelectric material tetragonal barium titanate. Piezoelectric materials are representatives of various types of catalytic conversion of external energy. The piezoelectric potential inside the piezoelectric body controls the entire piezoelectric catalytic process. The built-in piezoelectric potential field works in an indirect manner, mainly by adjusting the semiconductor properties, including manipulating the body energy band tilt, thereby providing a spatial driving force for the separation and conduction of charge carriers.

[0016] (2) The method of the present invention uses carboxylated multi-walled carbon nanotube powder and common piezoelectric material barium titanate powder as precursor reagents, and adopts ball milling dispersion technology to prepare piezoelectric material-carbon nanotube composite catalyst. In the prepared catalyst, carbon nanotubes and piezoelectric material barium titanate are evenly distributed, and the porous structure of nanotubes is widely present between the catalysts. The volume of the catalyst does not change much before and after ball milling, and has surface properties similar to those of carbon materials such as graphene, Ketjen black, and acetylene black, such as high strength, high conductivity, high thermal conductivity, chemical stability, and low density, while exhibiting piezoelectric catalytic characteristics. The piezoelectric material-carbon nanotube composite catalyst prepared by this method not only reflects the catalytic properties of intrinsic transition metal oxides, but also has the piezoelectric catalytic effect of barium titanate triggered by the internal stress generated during the evolution of sulfur into lithium sulfide, and has good application prospects in the positive electrode active material carrier for lithium-sulfur batteries.

[0017] (3) The piezoelectric material-carbon nanotube composite catalyst prepared by the present invention forms a carbon nanotube matrix with a high aspect ratio, on which the piezoelectric material tetragonal barium titanate is loaded. The piezoelectric material-carbon nanotube composite catalyst structure has a plurality of electron-ion network channels; there is a hollow structure between the network channels, which can achieve the control of polysulfide ions in the electrolyte through physical confinement, and the carbon tubes with a high aspect ratio have a guiding effect on electrons or metal ions; they directly contact the surface of the active material and enhance the conductivity of the active material. Applying it to lithium-sulfur batteries can effectively alleviate the effects of slow electrochemical reaction kinetics, shuttle effect and volume expansion on battery cycle performance, thereby utilizing the piezoelectric effect to improve the problem of low capacity of lithium-sulfur batteries caused by shuttle effect and slow electrochemical reaction kinetics.

[0018] (4) The present invention also uses ultrasound to further enhance the piezoelectric effect to solve the defect of poor cycle performance due to volume expansion during the sulfur redox process of the active substance. The ultrasonic external field can drive the formation and rupture of bubbles in the fluid medium through vibration to generate pressure waves, transferring momentum to the substances evenly distributed in the medium. The power gradient triggers the piezoelectric catalysis and the internal piezoelectric field to effectively suppress the shuttle effect during the electrocatalytic process.

[0019] (5) The method of the present invention adopts ball milling dispersion technology. By controlling the composite ratio of the piezoelectric material barium titanate and the carbon matrix, changing the speed parameter, temperature parameter, and time parameter during the double-axis mixing process before low-temperature sulfur melting, and subsequently applying ultrasonic conditions to the battery, the overall conductivity and surface structure of the positive electrode inside the battery can be compositely regulated. This method can simply, conveniently and scalably construct an internal stress-triggered and ultrasonically enhanced piezoelectric catalytic assisted lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is an X-ray diffraction spectrum; wherein, Figure A is an X-ray diffraction spectrum of the piezoelectric material-carbon nanotube composite catalyst prepared in Example 1 and the pure carbon phase carbon nanotube catalyst prepared in Comparative Example 1; Figure B is an X-ray diffraction spectrum of the ferroelectric material-carbon nanotube composite catalyst prepared in Comparative Example 2 and the pure carbon phase carbon nanotube catalyst prepared in Comparative Example 1; Figure 2 Fourier transform infrared spectra of the piezoelectric material-carbon nanotube composite catalyst prepared in Example 1, the pure carbon phase carbon nanotube catalyst prepared in Comparative Example 1, and the ferroelectric material-carbon nanotube composite catalyst prepared in Comparative Example 2; Figure 3 The Raman spectra of the piezoelectric material-carbon nanotube composite catalyst prepared in Example 1, the pure carbon phase carbon nanotube catalyst prepared in Comparative Example 1, and the ferroelectric material-carbon nanotube composite catalyst prepared in Comparative Example 2; Figure 4 The electron microscope scanning images are of the piezoelectric material-carbon nanotube composite catalyst prepared in Example 1 and the ferroelectric material-carbon nanotube composite catalyst prepared in Comparative Example 2; wherein Figure A is tetragonal barium titanate; Figure B is piezoelectric material-carbon nanotube composite catalyst; Figure C is cubic barium titanate; Figure D is ferroelectric material-carbon nanotube composite catalyst; Figure 5 Electrochemical impedance test results of lithium-sulfur batteries assembled in Examples 1-3 and Comparative Examples 1-3; Figure 6 Electrochemical impedance test results of lithium-sulfur batteries assembled in Examples 1-3 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0021] The following examples are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0022] Example 1 A method for preparing a piezoelectric catalytically assisted lithium-sulfur battery comprises the following steps: (1) 0.35 g of carboxylated multi-walled carbon nanotube powder (purity of 99%, particle size of 4 nm, length of 30 μm, oxygen content > 5 wt%) and 0.15 g of tetragonal barium titanate powder (BTO-T, particle size of 50 nm) were mixed, and then placed in a ball mill together with zirconium beads, and ball milled and dispersed at 26 ° C and 3000 rpm for 4 h to obtain a piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T); (2) Mixing elemental nano-sulfur powder (particle size of 100 nm) and piezoelectric material-carbon nanotube composite catalyst to prepare S / C / BTO-T mixture, then melting 0.45 g of S / C / BTO-T mixture at 165°C for 18 h (heating rate of 5°C / min), then adding 0.05 g of polyvinylidene fluoride (PVDF), mixing well, adding 1.6 g of N-methylpyrrolidone (NMP), and then stirring at 2000 rpm in a double-shaft mixer for 2 h to prepare positive electrode slurry; coating the positive electrode slurry on the surface of aluminum foil to form a 250 μm thick wet film, vacuum drying, and cutting it into positive electrode sheets with a diameter of 13 mm using a cutting machine; wherein the mass ratio of elemental nano-sulfur powder to piezoelectric material-carbon nanotube composite catalyst is 3:1; (3) Using the cathode sheet prepared in step (2), a lithium-sulfur battery is assembled in an argon-protected and dry glove box in the order of cathode sheet, diaphragm, lithium sheet, gasket and shrapnel. The battery accessories are 2032 button cells, the diaphragm is Celgrad 2500 diaphragm, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte of 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt% LiNO3 (LiTFSI is dissolved in a mixed solution of ethylene glycol dimethyl ether and 1,3-dioxolane, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1); after assembly, 720W ultrasound is applied in a constant temperature ultrasonic machine at 28°C for electrochemical testing.

[0023] Example 2 A method for preparing a piezoelectric catalytically assisted lithium-sulfur battery comprises the following steps: (1) 0.7 g of carboxylated multi-walled carbon nanotube powder (purity of 99%, diameter of 4 nm, length of 30 μm, oxygen content > 5 wt%) and 0.3 g of tetragonal barium titanate powder (BTO-T, 50 nm particle size) were mixed, and then placed in a ball mill together with zirconium beads and ball milled at 26 ° C and 3000 rpm for 3 h to prepare a piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T); (2) Mixing elemental nano-sulfur powder (particle size of 100 nm) and piezoelectric material-carbon nanotube composite catalyst to prepare S / C / BTO-T mixture, then melting 0.9 g of the S / C / BTO-T mixture at 170°C for 24 h (heating rate of 3°C / min), then adding 0.1 g of polyvinylidene fluoride (PVDF), mixing well, adding 2.1 g of N-methylpyrrolidone (NMP), and then stirring at 2000 rpm in a double-shaft mixer for 3 h to prepare positive electrode slurry; coating the positive electrode slurry on the surface of aluminum foil to form a 250 μm thick wet film, and then vacuum drying and cutting it into positive electrode sheets with a diameter of 13 mm using a cutting machine; wherein the mass ratio of elemental nano-sulfur powder to piezoelectric material-carbon nanotube composite catalyst is 4:1; (3) Using the cathode sheet prepared in step (2), in an argon-protected and dry glove box, assemble a lithium-sulfur battery in the order of cathode sheet, diaphragm, lithium sheet, gasket and shrapnel. The battery accessories are 2032 button cells, the diaphragm is Celgrad 2500 diaphragm, and the electrolyte used for battery assembly is a 1M lithium bistrifluoromethylsulfonimide (LiTFSI) lithium-sulfur electrolyte containing 2wt% LiNO3 (LiTFSI is dissolved in a mixed solution of ethylene glycol dimethyl ether and 1,3-dioxolane, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1); after assembly, apply 180W ultrasound in a constant temperature ultrasonic machine at 28°C for electrochemical testing.

[0024] Example 3 A method for preparing a piezoelectric catalytically assisted lithium-sulfur battery comprises the following steps: (1) 0.35 g of carboxylated multi-walled carbon nanotube powder (purity of 99%, diameter of 4 nm, length of 30 μm, oxygen content > 5 wt%) and 0.15 g of tetragonal barium titanate powder (BTO-T, 50 nm particle size) were mixed, and then placed in a ball mill together with zirconium beads and ball milled at 26 ° C and 3000 rpm for 3 h to prepare a piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T); (2) Mixing elemental nano-sulfur powder (particle size of 100 nm) and piezoelectric material-carbon nanotube composite catalyst to prepare S / C / BTO-T mixture, then melting 0.45 g of S / C / BTO-T mixture at 175 ° C for 12 h (heating rate of 10 ° C / min), then adding 0.05 g of polyvinylidene fluoride (PVDF), mixing well, adding 1.9 g of N-methylpyrrolidone (NMP), and then stirring at 2000 rpm in a double-shaft mixer for 2 h to prepare positive electrode slurry; coating the positive electrode slurry on the surface of aluminum foil to form a 250 μm thick wet film, and after vacuum drying, cutting it into positive electrode sheets with a diameter of 13 mm using a cutting machine; wherein the mass ratio of elemental nano-sulfur powder to piezoelectric material-carbon nanotube composite catalyst is 5:1; (3) Using the cathode sheet prepared in step (2), in an argon-protected and dry glove box, assemble a lithium-sulfur battery in the order of cathode sheet, diaphragm, lithium sheet, gasket and shrapnel. The battery accessories are 2032 button cells, the diaphragm is Celgrad 2500 diaphragm, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte of 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt% LiNO3 (LiTFSI is dissolved in a mixed solution of ethylene glycol dimethyl ether and 1,3-dioxolane, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1); after assembly, 360W ultrasound is applied in a constant temperature ultrasonic machine at 28°C for electrochemical testing.

[0025] Comparative Example 1 A method for preparing a lithium-sulfur battery comprises the following steps: (1) 0.7 g of carboxylated multi-walled carbon nanotube powder with a purity of 99%, a diameter of 4 nm, a length of 30 μm, and an oxygen content of >5 wt% was placed in a ball mill together with zirconium beads, and ball milled and dispersed at 26°C and 3000 rpm for 3 h to obtain a pure carbon phase carbon nanotube catalyst (MWCNT); (2) Mixing elemental nano-sulfur powder (particle size of 100 nm) and pure carbon phase carbon nanotube catalyst to prepare an S / C mixture, then melting 0.9 g of the S / C mixture at 155°C for 18 h (heating rate of 5°C / min), then adding 0.1 g of polyvinylidene fluoride (PVDF), mixing well, adding 1.4 g of N-methylpyrrolidone (NMP), and then stirring at 2000 rpm in a double-shaft mixer for 1 h to prepare a positive electrode slurry; coating the positive electrode slurry on the surface of aluminum foil to form a 250 μm thick wet film, vacuum drying, and cutting it into a positive electrode sheet with a diameter of 13 mm using a cutting machine; wherein the mass ratio of elemental nano-sulfur powder to pure carbon phase carbon nanotube catalyst is 3:1; (3) Using the cathode sheet prepared in step (2), in an argon-protected and dry glove box, assemble a lithium-sulfur battery in the order of cathode sheet, diaphragm, lithium sheet, gasket and shrapnel. The battery accessories are 2032 button cells, the diaphragm is Celgrad 2500 diaphragm, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte of 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt% LiNO3 (LiTFSI is dissolved in a mixed solution of ethylene glycol dimethyl ether and 1,3-dioxolane, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1); after assembly, electrochemical testing is carried out in a 28°C constant temperature box.

[0026] Comparative Example 2 A method for preparing a lithium-sulfur battery comprises the following steps: (1) 0.7 g of carboxylated multi-walled carbon nanotube powder (purity of 99%, diameter of 4 nm, length of 10 μm, oxygen content > 5 wt%) and 0.3 g of cubic barium titanate powder (BTO-C, 50 nm particle size) were mixed, and then placed in a ball mill together with zirconium beads, and ball milled and dispersed at 26 ° C and 3000 rpm for 3 h to obtain a ferroelectric material-carbon nanotube composite catalyst (CNT+BTO-C); (2) Mixing elemental nano-sulfur powder (with a particle size of 100 nm) and a ferroelectric material-carbon nanotube composite catalyst to prepare a S / C / BTO-C mixture, then melting 0.9 g of the S / C / BTO-C mixture at 155°C for 12 h (heating rate of 5°C / min), adding 0.1 g of polyvinylidene fluoride (PVDF), mixing well, adding 2.3 g of N-methylpyrrolidone (NMP), and stirring at 2000 rpm in a double-shaft mixer for 1 h to prepare a positive electrode slurry; coating the positive electrode slurry on the surface of an aluminum foil to form a 250 μm thick wet film, vacuum drying, and cutting it into a positive electrode sheet with a diameter of 13 mm using a sheet cutter; wherein the mass ratio of elemental nano-sulfur powder to ferroelectric material-carbon nanotube composite catalyst is 3:1; (3) Using the cathode sheet prepared in step (2), in an argon-protected and dry glove box, assemble a lithium-sulfur battery in the order of cathode sheet, diaphragm, lithium sheet, gasket and shrapnel. The battery accessories are 2032 button cells, the diaphragm is Celgrad 2500 diaphragm, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte of 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt% LiNO3 (LiTFSI is dissolved in a mixed solution of ethylene glycol dimethyl ether and 1,3-dioxolane, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1); after assembly, electrochemical testing is carried out in a 28°C constant temperature box.

[0027] Comparative Example 3 A method for preparing a piezoelectric catalytically assisted lithium-sulfur battery comprises the following steps: (1) 0.35 g of carboxylated multi-walled carbon nanotube powder (purity of 99%, diameter of 4 nm, length of 30 μm, oxygen content > 5 wt%) and 0.15 g of tetragonal barium titanate powder (BTO-T, 50 nm particle size) were mixed, and then placed in a ball mill together with zirconium beads, and ball milled and dispersed at 26 ° C and 3000 rpm for 3 h to obtain a piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T); (2) Mixing elemental nano-sulfur powder (particle size of 100 nm) and piezoelectric material-carbon nanotube composite catalyst to prepare S / C / BTO-T mixture, then melting 0.45 g of S / C / BTO-T mixture at 160°C for 24 h (heating rate of 5°C / min), then adding 0.05 g of polyvinylidene fluoride (PVDF), mixing well, adding 1.5 g of N-methylpyrrolidone (NMP), and then stirring at 2000 rpm in a double-shaft mixer for 1 h to prepare positive electrode slurry; coating the positive electrode slurry on the surface of aluminum foil to form a 250 μm thick wet film, and after vacuum drying, cutting it into positive electrode sheets with a diameter of 13 mm using a cutting machine; wherein the mass ratio of elemental nano-sulfur powder to piezoelectric material-carbon nanotube composite catalyst is 3:1; (3) Using the cathode sheet prepared in step (2), in an argon-protected and dry glove box, assemble a lithium-sulfur battery in the order of cathode sheet, diaphragm, lithium sheet, gasket and shrapnel. The battery accessories are 2032 button cells, the diaphragm is Celgrad 2500 diaphragm, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte of 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt% LiNO3 (LiTFSI is dissolved in a mixed solution of ethylene glycol dimethyl ether and 1,3-dioxolane, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:1); after assembly, electrochemical testing is carried out in a 28°C constant temperature box.

[0028] Experimental Example 1 Characterization of piezoelectric material-carbon nanotube composite catalyst (1) The X-ray diffraction spectra of the piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T) prepared in Example 1, the pure carbon phase carbon nanotube catalyst (MWCNT) prepared in Comparative Example 1, and the ferroelectric material-carbon nanotube composite catalyst (CNT+BTO-C) prepared in Comparative Example 2 are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that after the piezoelectric material-carbon nanotube composite catalyst prepared in Example 1 was dispersed by ball milling, neither the carboxylation multi-walled carbon nanotube phase nor the barium titanate phase showed obvious shift, that is, there was neither disappearance of existing peaks nor appearance of new peaks, indicating that the carboxylation multi-walled carbon nanotubes and the barium titanate material of the piezoelectric material-carbon nanotube composite catalyst in Example 1 were physically mixed.

[0029] (2) The Fourier transform infrared spectra of the piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T) prepared in Example 1, the pure carbon phase carbon nanotube catalyst (MWCNT) prepared in Comparative Example 1, and the ferroelectric material-carbon nanotube composite catalyst (CNT+BTO-C) prepared in Comparative Example 2 are shown in FIG. Figure 2 As shown. Figure 2It can be seen that the spectrum of the piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T) prepared in Example 1 shows the properties of carbon-based materials, containing carbon-carbon double bonds and carbon-oxygen double bonds, and the presence of polar groups can effectively capture polysulfides during the electrochemical reaction and promote electrochemical behavior kinetically. After ball milling dispersion, neither the ferroelectric material-carbon nanotube composite catalyst nor the piezoelectric material-carbon nanotube composite catalyst showed obvious deviation, and there was no disappearance of existing peaks nor the appearance of new peaks, which further shows that the ball milling process is a physical process.

[0030] (3) The Raman spectra of the piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T) prepared in Example 1, the pure carbon phase carbon nanotube catalyst (MWCNT) prepared in Comparative Example 1, and the ferroelectric material-carbon nanotube composite catalyst (CNT+BTO-C) prepared in Comparative Example 2 are shown in FIG. Figure 3 As shown, the two large peaks on the left and right are the D peak and G peak of the Raman spectrum. The more obvious the D peak is, the more defects there are in the carbon material, and the more obvious the G peak is, the more SP 2 The more structures. Figure 3 It can be seen that the Raman spectrum test results of the piezoelectric material-carbon nanotube composite catalyst prepared in Example 1 show that there are a large number of defects in the carbon body, and these defects can provide more active sites in the redox reaction process. After ball milling dispersion, neither the ferroelectric material-carbon nanotube composite catalyst nor the piezoelectric material-carbon nanotube composite catalyst showed obvious deviation, and there was no disappearance of existing peaks nor the appearance of new peaks, which further shows that the ball milling process is a physical process.

[0031] (4) The electron microscope scanning images of the piezoelectric material-carbon nanotube composite catalyst (CNT+BTO-T) prepared in Example 1 and the ferroelectric material-carbon nanotube composite catalyst (CNT+BTO-C) prepared in Comparative Example 2 are as follows: Figure 4 As shown. Figure 4 As shown in Figures C and D, both the ferroelectric material-carbon nanotube composite catalyst and the piezoelectric material-carbon nanotube composite catalyst show a particle size of about 50 nm. After ball milling dispersion, both the ferroelectric material-carbon nanotube composite catalyst and the piezoelectric material-carbon nanotube composite catalyst show a microscopic morphology of uniform dispersion of barium titanate materials in complex carbon nanotubes, without obvious agglomerates, indicating effective dispersion during the ball milling process.

[0032] Test Example 2: Lithium-sulfur battery electrochemical test (1) The electrochemical impedance test was performed on the lithium-sulfur batteries assembled in Examples 1-3 and Comparative Examples 1-3. The results are as follows: Figure 5 As shown. Figure 5It can be seen that the addition of barium titanate material reduces the overall interface charge transfer resistance, and the ion transfer rate is also significantly improved, indicating that the addition of barium titanate can effectively improve the internal ion and electron transport of lithium-sulfur batteries. Among them, compared with the ferroelectric material-carbon nanotube composite catalyst, the interface resistance of the piezoelectric material-carbon nanotube composite catalyst is lower, indicating that the piezoelectric effect is effectively catalytically reflected in the lithium-sulfur battery. By comparing the impedance spectra of different ultrasonic powers, it can be seen that the application of ultrasound can effectively enhance the above-mentioned piezoelectric catalytic process. It is worth noting that higher power will further reduce the resistance.

[0033] (2) The lithium-sulfur batteries assembled in Examples 1-3 and Comparative Examples 1-3 were subjected to cyclic voltammetry at a scan rate of 0.1 mV / s. The current-voltage curves were as follows: Figure 6 As shown. Figure 6 It can be seen that the addition of piezoelectric material-carbon nanotube composite catalyst has enhanced the overall electrochemical behavior, both in the oxidation and reduction processes, and the redox reaction potential has also been significantly reduced, indicating that the addition of barium titanate can effectively improve the polysulfide transformation process inside the lithium-sulfur battery. Compared with the ferroelectric material-carbon nanotube composite catalyst, the peak current of the piezoelectric material-carbon nanotube composite catalyst group is higher, indicating the catalytic manifestation of the piezoelectric effect in lithium-sulfur batteries. By comparing the cyclic voltammetry test diagrams of different ultrasonic powers, it can be seen that the application of ultrasound can effectively regulate the above-mentioned piezoelectric catalytic process. It is worth noting that the highest power performs best, further improving the peak current and regulating the redox reaction potential.

[0034] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A piezoelectric material-carbon nanotube composite catalyst, characterized in that: It comprises carboxylated multi-walled carbon nanotube powder and tetragonal barium titanate powder; wherein the purity of the carboxylated multi-walled carbon nanotube is 80%-99%, the diameter is 4nm-10nm, the length is 5μm-30μm, and the oxygen content is>5wt%; the particle size of the tetragonal barium titanate powder is 20nm-500nm, and the microscopic morphology is stick-shaped or spherical; the mass ratio of the carboxylated multi-walled carbon nanotube powder to the tetragonal barium titanate powder is 7:1-14.

2. The method for preparing the piezoelectric material-carbon nanotube composite catalyst according to claim 1, characterized in that: The following steps are involved: The carboxyl multi-walled carbon nanotube powder and tetragonal barium titanate powder are mixed and ball-milled to obtain the product.

3. The method for preparing the piezoelectric material-carbon nanotube composite catalyst according to claim 2, characterized in that: The ball milling is carried out at 10°C-50°C and 1000rpm-30000rpm; the single working time of the ball milling is 10min-20min, and the intermittent time is 10min-30min; the total time of the ball milling is 3h-12h.

4. A lithium-sulfur battery, characterized in that: It includes the piezoelectric material-carbon nanotube composite catalyst as claimed in claim 1.

5. The lithium-sulfur battery according to claim 4, characterized in that: The lithium-sulfur battery is a button cell or a soft pack cell.

6. The method for preparing a lithium-sulfur battery according to any one of claims 4 to 5, characterized in that: The following steps are involved: (1) Mixing active sulfur and the piezoelectric material-carbon nanotube composite catalyst according to claim 1 or 2, and then heating to perform low-temperature sulfur melting to obtain a S / C / BTO-T mixture; (2) adding a binder and a solvent to the S / C / BTO-T mixture obtained in step (1), mixing them evenly, and preparing a positive electrode slurry; (3) coating the positive electrode slurry obtained in step (2) on the surface of the positive electrode material, and then cutting the positive electrode material into pieces to obtain a positive electrode sheet; (4) Assemble the lithium-sulfur battery in the order of positive electrode sheet, separator, lithium sheet, gasket and shrapnel, and then perform ultrasonic treatment.

7. The method for preparing a lithium-sulfur battery according to claim 6, characterized in that: The time for low-temperature sulfur melting in step (1) is 20-24 hours, the temperature is 155°C-195°C, and the heating rate is 3°C / min-10°C / min.

8. The method for preparing a lithium-sulfur battery according to claim 6, characterized in that: The active sulfur in step (1) is single-substance nano-sulfur powder with a size of 80-100 nm; the mass ratio of the active sulfur to the piezoelectric material-carbon nanotube composite catalyst is 3-5:

1.

9. The method for preparing a lithium-sulfur battery according to claim 6, characterized in that: In step (2), the binder is polyvinylidene fluoride or LA133 type water-based adhesive; and the solvent is N-methylpyrrolidone or water.